Microdissection and Single-Cell Suspension of Neocortical Layers From Ferret Brain for Single-Cell Assays - Lucia Del-Valle-Anton; Salma Amin; Víctor Borrell (Bio-Protocol)
Brain development is highly complex and dynamic. During this process, the different brain structures acquire new components, such as the cerebral cortex, which builds up different germinal and cortical layers during its development. The genetic study of this complex structure has been commonly approached by bulk-sequencing of the entire cortex as a whole. Here, we describe the methodology to study this layered tissue in all its complexity by microdissecting two germinal layers at two developmental time points. This protocol is combined with a step-by-step explanation of tissue dissociation that provides high-quality cells ready to be analyzed by the newly developed single-cell assays, such as scRNA-seq, scATAC-seq, and TrackerSeq. Altogether, this approach increases the resolution of the genetic analyses from the cerebral cortex compared to bulk studies. It also facilitates the study of laboratory animal models that recapitulate human cortical development better than mice, like ferrets.